ON THE SPECTROPHOTOMETRIC STAR CATALOGUE - Dragunova, A. V.; Karamysh, V. F.; Komarov, N. S. (Одеські астрономічні публікації, 2017)
The data on energy distributions in spectra of 555 stars are reduced to one system and averaged. The results of stellar spectrophotometry are used which have been obtained at astronomical institutions in Moscow (Sternberg Astronomical Institute), S.-Petersburg (Main AO RAS), Alma - Ata (Astrophysical Institute), Crimea (Simpheropol State University, CrAO), Odessa (OAO) during 25 recent years. For only 180 stars the scatter of individual data (of catalogues) does not exceed 10in all the considered wavelength range (320-1080 nm) for B - M spectral types.